Presence of different genotypes of Helicobacter pylori in patients with chronic tonsillitis and sleep apnoea syndrome - Nártová, Eva; Kraus, Jaroslav; Pavlík, Emil; Lukeš, Petr; Katra, Rami; Plzák, Jan; Kolářová, Libuše; Sterzl, Ivan; Betka, Jan; Astl, Jaromír (European archives of oto-rhino-laryngology, 2014)
Helicobacter pylori, a well-known gastric pathogen, has been detected in the oral cavity and oropharynx in tonsillar tissue. In our study, the presence of H. pylori in the tonsillar tissue of patients with chronic tonsillitis and sleep apnoea syndrome (SAS) was investigated. The aim was to detect and genotype H. pylori for a collection of data supporting the possible role of H. pylori in the aetiology of chronic tonsillitis and SAS. Helicobacter pylori was detected by real-time polymerase chain reaction (rt-PCR). 89 patients, 60 with a diagnosis of chronic tonsillitis and 29 with SAS, were tested. In the chronic tonsillitis group, Helicobacter was detected in 48 (80 %) specimens, cagA gene was detected in 12 samples (25 %) and 12 samples were negative. In SAS group, Helicobacter was found in 24 samples (82.76 %), cagA gene was detected in 5 (20.83 %) and 5 samples (17.24 %) were negative. Helicobacter pylori-specific immunoglobulins were tested by ELISA in the serum of 57 patients only with 41 (71.93 %) showing positive. Our results on H. pylori DNA detection and H. pylori seropositivity show 26.32 % discrepancy, slightly in favour of rt-PCR (15.79 % compared to 10.53 %). The H. pylori presence in tonsillar tissue does not depend on the type of oropharyngeal disease (p = 0.756). This study shows that oropharynx constitutes an extragastric reservoir of H. pylori infection which could serve as an aetiopathogenetic factor for chronic tonsillitis and tonsillar hyperplasia by SAS. No conclusion has yet been drawn about the mechanism of the process.
Keywords: senioři; protilátky bakteriální; Sleep Apnea Syndromes; Palatine Tonsil; Real-Time Polymerase Chain Reaction; genotyp; DNA, Bacterial; Helicobacter Infections; Tonsillectomy; Genotype; Chronic Disease; Cohort Studies; syndromy spánkové apnoe; chronická nemoc; Middle Aged; mužské pohlaví; Adult; mladý dospělý; krční mandle; kohortové studie; Tonsillitis; kvantitativní polymerázová řetězová reakce; infekce vyvolané Helicobacter pylori; DNA bakterií; Young Adult; ženské pohlaví; ELISA; Humans; Antibodies, Bacterial; lidé středního věku; Helicobacter pylori; Enzyme-Linked Immunosorbent Assay; dospělí; Female; tonzilitida; Aged; tonzilektomie; lidé; Male